European Society for Immunodeficiencies guidelines for the management of patients with congenital athymia - Kreins, Alexandra Y; Dhalla, Fatima; Flinn, Aisling M; Howley, Evey; Ekwall, Olov; Villa, Anna; Staal, Frank J T; Anderson, Graham; Gennery, Andrew R; Holländer, Georg A; Davies, E Graham; European Society for Immunodeficiencies Clinical Working Party (The Journal of allergy and clinical immunology, 2024)
Congenital athymia is a life-limiting disorder due to rare inborn errors of immunity causing impaired thymus organogenesis or abnormal thymic stromal cell development and function. Athymic infants have a T-lymphocyte-negative, B-lymphocyte-positive, natural killer cell-positive immunophenotype with profound T-lymphocyte deficiency and are susceptible to severe infections and autoimmunity. Patients variably display syndromic features. Expanding access to newborn screening for severe combined immunodeficiency and T lymphocytopenia and broad genetic testing, including next-generation sequencing technologies, increasingly facilitate their timely identification. The recommended first-line treatment is allogeneic thymus transplantation, which is a specialized procedure available in Europe and the United States. Outcomes for athymic patients are best with early diagnosis and thymus transplantation before the development of infectious and inflammatory complications. These guidelines on behalf of the European Society for Immunodeficiencies provide a comprehensive review for clinicians who manage patients with inborn thymic stromal cell defects; they offer clinical practice recommendations focused on the diagnosis, investigation, risk stratification, and management of congenital athymia with the aim of improving patient outcomes.
Keywords: Thymus Gland; Congenital athymia; syndromy imunologické nedostatečnosti; Disease Management; DiGeorge syndrome; thymus transplantation; lidé; Europe; Infant, Newborn; Evropa; 22q11.2 deletion syndrome; Immunologic Deficiency Syndromes; novorozenec; immunology guidelines; thymus; management nemoci; Humans